Integration Of Basic Curriculum And Lifeskill Curriculum In Nature School Curriculum Development - Noviyanti, Aliya; Hadiana, Eri; Siregar, Hariman Surya (PT. Student Rihlah Indonesia, 2025)
The purpose of this study is to determine the curriculum development model at Sekolah Alam. The research method used is descriptive qualitative research with a case study method. Data collection consists of observation, interviews, and documentation. The results of the study indicate that Sekolah Alam Bandung has a unique curriculum development model based on student psychology. At the secondary school level, the curriculum is developed through the integration of the basic curriculum and the Lifeskill Curriculum in a 50:50 ratio. The Basic Curriculum provides preparation for higher education, covering core subjects for university entrance exams (PTN/PTS) and the SAT, using national education standards. The Lifeskill Curriculum is designed to prepare students for direct entry into the business or professional world, covering basic professional training from technical operator levels to managers and entrepreneurs. The methods of achievement include internships, business learning together, learning from masters, business outings, and other methods. The mandatory business fields that every student must go through are Business with an environmental perspective ‘Biotechnology’, future business tools ‘Information and Technology Information’, and commerce ‘Retail and Distribution’.